2014
DOI: 10.1071/sp14010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil nutrient management practices of taro farmers in Taveuni, Fiji

Abstract: There is evidence that the soil health in Taveuni, Fiji is deteriorating over time threatening livelihoods of taro producers. The present study was conducted to understand the soil nutrient management practices followed by taro farmers in Taveuni. The study revealed that the farmers in Taveuni use various organic and chemical fertilizers and various other soil fertility management practices such as mulching, crop rotation with legumes, yagona and agroforestry. The quantity of nitrogen, phosphorous and potash (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The importance of fertile soil in maintaining high crop yield is well documented (8)(9)(10)(11). Our study has also shown that the taro production in Taveuni, has deteriorated over time due to continuous plantation and indiscriminate and imbalanced fertilizer use (7).…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…The importance of fertile soil in maintaining high crop yield is well documented (8)(9)(10)(11). Our study has also shown that the taro production in Taveuni, has deteriorated over time due to continuous plantation and indiscriminate and imbalanced fertilizer use (7).…”
Section: Introductionsupporting
confidence: 50%
“…Before the cropping cycle of taro, Matei site showed high level of the soil K while Mua site showed sufficient level of the soil K. The soil K is easily lost from soils of fine texture such as clay and clay loam soils because of its availability in soluble and exchangeable forms. The soils in the four study sites are of clay to clay loam nature (7); hence K could have been easily leached through the soil, resulting in low and declining levels of soil K in the sites. The K contents in the present study for different soil samples are comparable to the literature values as mean topsoil K of taroexporting farms in Samoa as 234 mg kg À1 (34) and the mean soil K concentration between low-yielding orchards and between high-yielding orchards in Nagpur, India as 197.37 and 229.35 mg kg À1 , respectively (42) only for Matei site but much higher than in the soil samples from Mua, Vione and Delaivuna sites ( Table 5).…”
Section: Soil K Analysis During the Cropping Cyclementioning
confidence: 99%
See 1 more Smart Citation